Piracy in Somalia: An Analysis of the Challenges Faced by the International Community - Amali Kartika Karawita (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Piracy in Somalia is a phenomenon that has presented several challenges for the international community since the beginning of the 21st century. Effectively formulating a plan of action against piracy requires the willingness of the international community to work together by implementing strong multilateral operations between countries and understanding the social and economic difficulties faced by Somalia, which has given rise to the endemic and its expansion throughout the region. Eradicating piracy means tackling the issue on land by confronting Somalia’s extreme poverty and lack of economic opportunity as well as creating a comprehensive legal framework that will serve as a model to fight piracy. The objective of the present paper is to discuss the roots of piracy in Somalia and the cycle it created, as well as provide an analysis on the legal framework in place in order to judge its effectiveness on an international level. The method applied to lead this research is based on the analysis of reports from international bodies such as the UN and the ICC, as well as academic articles. The results have shown that piracy is the fruit of social, economic, and political issues that have enabled the phenomenon to spread and establish itself in the country.